I want to be a firefighter. (Ontario, Canada : Firefly Press, 1999)
Provides a simple introduction to the work that firefighters do, their equipment and gear, and other aspects of a firefighter's life.
Keywords: Fire fighters -- Juvenile literature; Fire extinction -- Juvenile literature